Comparison of physicochemical properties of biochars and hydrochars produced from food wastes. (1st November 2019) - Fu, Ming-Ming; Mo, Ce-Hui; Li, Hui; Zhang, Ya-Nan; Huang, Wei-Xiong; Wong, Ming Hung
Abstract: Tremendous amounts of food wastes are produced in China, and the conventional treatment by landfilling and incineration approaches poses serious environmental and social threats. Carbonization of food waste into value-added bio-solid is a feasible and potential alternative method for its sustainably recycle. Very limited information is available on the variation in biochar and hydrochar produced from food waste. In this study, five typical food waste types (eggshell, fish residue, breadcrumb, cooked rice and mixed food waste) and seven temperatures (200, 300, 400, and 500 °C for pyrolysis and 200, 250, and 300 °C for hydrothermal carbonization) were used, and physicochemical characteristics of the biochars and hydrochars were characterized. The main mass loss occurred centering at the temperatures of 270–320 °C, and 400 °C was a critical temperature for a complete decomposition. Physically, hydrochars showed spherically shaped morphological features in comparison with the pore and crack structures of biochars. Specific surface areas were generally low (<2 m 2 /g) for biochar and hydrochars produced from food wastes, except for biochar produced from mixed food waste at 500 °C (18 m 2 /g) and hydrochars produced from cooked rice at 300 °C (54 m 2 /g). In terms of chemical properties, hydrochars differed in pH, functional groups, elemental composition, proximate analysis compared with biochars. Hydrochars showed similar functional group types to that of biochars at low peak temperatures (≤300 °C), but the functional groups for biochars nearly disappeared at higher temperatures (≥400 °C). Hydrochars showed lower polarity and aromaticity than that of biochars. Hydrochars showed a lower pH and ash content than biochars due to the washout of inorganic components during hydrothermal carbonization. The results from this study proved the feasibility of recycling food wastes through pyrolysis and hydrothermal carbonization, and provided basic information for their potential utilization. Highlights: Food wastes were converted into biochars and hydrochars through pyrolysis and hydrothermal carbonization. Biochars and hydrochars produced from food wastes showed comparable properties compared with conventional biochars. Na concentrations in biochar and hydrochars produced from food wastes were limited.